CuO Nano-structures Prepared in Rosmarinus Officinalis Leaves Extract Medium: Efficient Catalysts for the Aqueous Media Preparation of Dihydropyrano[3, 2-c]chromene Derivatives - Ghashang, Majid; Kargar, Mahboubeh; R.M. Shafiee, Mohammad; S. Mansoor, Syed; Fazlinia, Abbas; Esfandiari, Hadi (Recent Patents on Nanotechnology, 2015)
CuO nano-structures were prepared in Rosmarinus Officinalis leaves extract medium via a green bio-chemical method and were used for the one-pot synthesis of dihydropyrano [3,2-c] chromene derivatives. This procedure is very simple and the products were synthesized in high to excellent yields.
Keywords: biosyntheis